2021
DOI: 10.1093/noajnl/vdab110
|View full text |Cite
|
Sign up to set email alerts
|

Low tumor cell content predicts favorable prognosis in germinoma patients

Abstract: Background Germinoma preferentially occurs in pediatric and young adult age groups. Although they are responsive to treatment with chemotherapy and radiation, the treatment may cause long-term sequelae in their later lives. Here, we searched for clinical and histopathological features to predict the prognosis of germinoma and affect treatment response. Methods A total of 114 germinoma cases were included in the analysis. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…One of the novel aspects of evaluating and stratifying germinoma treatment strategies is that cases with many immune cells have shown better prognoses than those with a high tumor content in previous research ( 28 ). Moreover, this finding remained statistically significant when incorporating information on tumor location, as tumor location is another prognosis-related factor, as described previously ( 29 ). Currently, it is not standard practice to only treat germinoma with chemotherapy without radiation therapy, based on the results of previous clinical trials in which frequent relapses were observed in patients with germinoma treated with chemotherapy only ( 30 ).…”
Section: Germinomasupporting
confidence: 83%
See 2 more Smart Citations
“…One of the novel aspects of evaluating and stratifying germinoma treatment strategies is that cases with many immune cells have shown better prognoses than those with a high tumor content in previous research ( 28 ). Moreover, this finding remained statistically significant when incorporating information on tumor location, as tumor location is another prognosis-related factor, as described previously ( 29 ). Currently, it is not standard practice to only treat germinoma with chemotherapy without radiation therapy, based on the results of previous clinical trials in which frequent relapses were observed in patients with germinoma treated with chemotherapy only ( 30 ).…”
Section: Germinomasupporting
confidence: 83%
“…Most dominant immune cells are lymphocytes (T-cell and B-cell, approximately 60-70% on average) and natural killer cells, but immune cell repertoire in germinoma also includes myeloid-derived cells such as macrophages accounting for approximately 20-30% on average ( 28 ). The ratio between germinoma cells and immune cells is known to vary substantially depending on case characteristics, with <10% to 90% of tumor cells (out of all nucleated cells in tissue specimens) observed on hematoxylin-eosin (H-E) staining ( 29 ). As germinoma cells are obviously larger than immune cells and their cell morphologies differ, it would not be very challenging to calculate the ratio of tumor cells to immune cells in daily clinical practice.…”
Section: Germinomamentioning
confidence: 99%
See 1 more Smart Citation
“…Lower tumor cell content, typical location (neurohypophysis or pineal gland), and abundant infiltrating lymphocytes are significantly associated with a better prognosis of germinoma. 2 , 27 , 28 Interestingly, in the present study (Figure 4 ), HEVs density was significantly correlated with lower tumor cell content, not to mention their relationship with the amounts of T and B cells. Furthermore, our study also showed that all the HEV‐high tumors were located in the suprasellar and pineal regions.…”
Section: Discussionsupporting
confidence: 48%
“…However, several factors have been shown to possess prognosis signi cance for germinoma in previous studies. Lower Tumor cell content, typical location (neurohypophysis or pineal gland), and abundant in ltrating lymphocytes are signi cantly associated with a better prognosis of germinoma (2,27,28). Interestingly, in the present study, HEVs density was signi cantly correlated with lower tumor cell content, not to mention their relationship with the amounts of T and B cells.…”
Section: Discussionmentioning
confidence: 99%